A Study of Bacterial Causes and Factors Affecting Middle Ear Infection among Hearing Aid User in the City of Fallujah - mateab, Youssef Hussein Shajaa; Hammadi, Ahmed Khader Abbas; Ali, Ghufran Saud Abdullah; Khalifa, Shahad Sufyan (American Journal of Biology and Natural Sciences, 2024)
In this research, a group of samples were taken at Fallujah Hospital. By taking samples from patients with middle ear infections of different ages and for both sexes, it was found that the infection rate in the city is greater than the infection rate in the village. It was also noted that the infection rate in males is higher than in females.